Adaptive tuning of PID using chef‑based optimization algorithm for improving automatic voltage regulator - Widi Aribowo; Reza Rahmadian; Mahendra Widyartono (Institute of Advanced Engineering and Science, 2023)
This article presents the proportional-integral-derivative (PID) parameter tuning on the automatic voltage regulator (AVR) using the chef-based optimization algorithm (CBOA). CBOA is modeling cooking training activities consisting of students and young chefs in an effort to mature cooking skills. This article uses other methods as a comparison in measuring the performance of the proposed method. The methods used are grasshopper optimization algorithm (GOA) and cooperation search algorithm (CSA). The simulation results show that the proposed method, namely CBOA, has a better ability in the peak value of overshoot, which is 0.232% compared to the CSA method and 12.99% compared to the GOA method.